Effect Of Orthodontic Treatment On Gingival Health: An Observational Health (Journal of Pharmaceutical Negative Results, 2023)
Background: The present study was conducted fir evaluating the effect of orthodontic treatment on gingival health.Materials & methods: A total of 20 patients were enrolled who were scheduled to undergo fixed orthodontic treatment. Pre-treatment clinical examination was done. Complete demographic and clinical details of all the patients was done. Fixed orthodontic treatment was started. Clinical evaluation of all the patients was done after one month follow-up. All the results were recorded and effect of orthodontic treatment on gingival health was assessed. All the results were evaluated using SPSS software. Results: A total of 20 patients evaluated. Mean age of the patients was 21.5 years. Out of 20 patients, 12 patients were males while the remaining were females. Mean visible plaque, visible inflammation and gingival recession was significantly higher at follow-up in comparison to pre-treatment values.Conclusion: Fixed orthodontic treatment has significant effect on gingival tissue.